Analysis credit risk management minimizing performing loans to credit business people - Ida Nuryana (MBR (Management and Business Review), 2017)
Aim from research thisfor analyze application management risk credit in minimizing nonperforming loans in the People's Business Credit (KUR) in Bank Jatim Branch of Sidoarjo and to determine the application of credit risk management effective in minimizing the problem loansthe People's Business Credit (KUR) in Bank of Sidoarjo East Java. This type of research used in this research is descriptive research. The results showed that at Bank Jatim Branch of Sidoarjo has implemented well the active supervision of commissioners and directors, policies, procedures and limits, the process of identification, measurement, monitoring and management information system of credit risk, and credit risk control. This study suggested that banks maintain the independence of credit staff and also improve credit monitoring well